AN INVESTIGATION OF THE LINGUISTIC FEATURES OF COLLABORATIVELY WRITTEN TEXTS USING GOOGLE JAMBOARD - Hentasmaka, Daning; Aprilia, Laili Sintiya; Puspitasari, Yunita (PARADIGM: Journal of Language and Literary Studies, 2024)
Writing is the most challenging skill for students because it takes longer to develop and tends to cause problems, especially with linguistic features that characterize proficient writing. This study investigated the linguistic features of students who did collaborative writing using Google Jamboard and those without the application. A pre-experimental research with static group comparison was implemented. Two pre-existing groups of 34 students each were observed as the study sample. The experimental group wrote collaboratively using Google Jamboard, while the control group did not. The data on students' linguistic features – lexical, orthographic, grammatical – were collected from the collaborative writing results analyzed using the non-parametric Mann-Whitney U test. The analysis showed a significant difference in the mean ranks of the linguistic features between the two groups, in which the group facilitated by Google Jamboard showed superior performance in lexical and grammatical features but not in orthographic features compared to those who were not. Thus, it is suggested that Google Jamboard be implemented in collaborative writing to boost students' development of linguistic features.